2021
DOI: 10.3390/pharmaceutics13081114
|View full text |Cite
|
Sign up to set email alerts
|

Direct Powder Extrusion 3D Printing of Praziquantel to Overcome Neglected Disease Formulation Challenges in Paediatric Populations

Abstract: For the last 40 years, praziquantel has been the standard treatment for schistosomiasis, a neglected parasitic disease affecting more than 250 million people worldwide. However, there is no suitable paediatric formulation on the market, leading to off-label use and the splitting of commercial tablets for adults. In this study, we use a recently available technology, direct powder extrusion (DPE) three-dimensional printing (3DP), to prepare paediatric Printlets™ (3D printed tablets) of amorphous solid dispersio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 61 publications
0
36
0
Order By: Relevance
“…Entrapping by the printed polymers may be sufficient for taste masking of bitter compounds [30,31]. (c) High viscosity hydrophilic polymers may prevent fast hydration and dissolution of the dosage form, thereby reducing the migration to the taste receptors on the tongue and the resulting taste sensation.…”
Section: Taste Maskingmentioning
confidence: 99%
“…Entrapping by the printed polymers may be sufficient for taste masking of bitter compounds [30,31]. (c) High viscosity hydrophilic polymers may prevent fast hydration and dissolution of the dosage form, thereby reducing the migration to the taste receptors on the tongue and the resulting taste sensation.…”
Section: Taste Maskingmentioning
confidence: 99%
“…The concentration after 10 min of testing should not exceed the bitterness threshold concentration for successful taste-masking. Both studies concluded their formulations were sufficiently taste-masking [42,49]. Furthermore, when comparing the dissolution of the 3D-printed tablets in artificial saliva to tablets produced with direct compression, the directly compressed tablets fully released the drug in 50 s. This indicated no tastemasking of the directly compressed tablets [42].…”
Section: Palatable Oral Dosage Formsmentioning
confidence: 95%
“…Dose flexibility has also been achieved by altering the drug concentration in the tablet matrix [39,49], though a higher drug concentration could reduce the printability of the tablet matrix [49]. For inkjet printing and drop-on-solid 3D printing, the concentration of the drug in the printing ink can be altered to adjust to printed dose [52,55,56].…”
Section: Pediatric-centered Formulation Designmentioning
confidence: 99%
See 2 more Smart Citations